An Empirical Note on Perceptions of Partial Apologies - Mandeep Dhami (Oñati Socio-Legal Series)
This study examined perceptions of partial apologies. Eighty young people rated the extent to which five components of apology (i.e., accepting responsibility, acknowledging harm, expressing remorse, offering reparation, and promising forbearance) implied each other. Statistical analyses across different types of partial apologies showed no significant differences in the extent to which a particular uncommunicated component of apology was implied by one type of partial apology than another. Analyses within each type of partial apology revealed significant differences in the extent to a partial apology implied one type of uncommunicated component than another: Acknowledging harm or offering reparation implied promising forbearance to a lesser extent than accepting responsibility and expressing remorse. Expressing remorse or promising forbearance implied accepting responsibility to a greater extent than acknowledging harm and offering reparation. It is important to understand perceptions of partial apologies because they are more prevalent than full apologies, and may be considered less effective.